Extração de óleo da pimenta rosa (Schinus terebinthifolius Raddi) : compostos bioativos, cinética e atividade antioxidante - Alves, Fernanda Maslova Soares (2018)
The rose pepper (Schinus terenbithifolius Raddi) has drawn attention from producers and consumers in the northeast of Brazil for offering health benefits due to its compounds. Therefore, the antioxidant and kinetic activity of rose pepper oil extract (Schinus terenbithifolius Raddi) were evaluated in this work. Extractions with pure supercritical CO2 (SFE/CO2), supercritical CO2 with isopropanol (SFE/CO2 + C3H8O) and Soxhlet (SE) were carried out using methanol, ethanol and hexane solvents. In the supercritical fluid extraction process, a factorial 23 experimental design with replica in the central point was used, under process conditions with temperatures of 20, 40 and 60ºC, pressures of 15, 20 and 25 MPa and solvent flow of 2, 3 and 4 mL min-1 for SFE/CO2, 2, 4 and 6% isopropanol concentration and solvent flow set at 4 mL min-1 for SFE/CO2 + C3H8O. The extraction kinetics were evaluated at 20 MPa/40°C/3 mL min-1 for SFE/CO2 and 20 MPa/40°C/4% for SFE/CO2 + C3H8O. The models of Tan and Liou, Esquivel and Martínez were used to adjust the kinetic curve. The Martinez model best fit the kinetic curve, which resulted in a smaller mean relative error (mre). Among the extraction methods, the Soxhlet extraction using methanol as the solvent achieved the best results with an overall oil yield (28.62%). The best results of the antioxidant activity were: by the DPPH method (125.82, 452.30 and 408.68 μg mL-1), ABTS (68.25, 35.53 and 28.82 μMTEAC g-1 oil), (1424.85, 143.26 and 268.67 mgGAE 100g-1 of oil) which were obtained in the Soxhlet extraction oil samples using methanol solvent, pure supercritical CO2 and SFE/CO2 + C3H8O. The composition of the oil was evaluated by chromatography and some phenolic compounds were found: tocopherol, gallic acid, p-coumaric acid, trans-cinnamic acid and quercentin.